Administrative Resilience and Educational Continuity in Flood Prone Public Schools in Rivers State - Dagogo Alu Longjohn (INTERNATIONAL JOURNAL OF EDUCATION AND EVALUATION, 2026)
This study examined the relationship between administrative resilience and educational continuity in flood-prone public schools in Rivers State. The study was guided by two research questions and corresponding hypotheses, focusing on emergency preparedness and planning and resource management and mobilization. A correlational research design was adopted for the study. The population of the study was 1,899 administrative staff in 39 public senior secondary schools in Port Harcourt Metropolis, Rivers State. There was no sampling. Data were collected using two structured questionnaires titled: “Administrative Resilience Questionnaire ARQ” and “Educational Continuity Questionnaire ECQ” designed on a 4-point Likert scale (SA–SD). The two questionnaires were validated by experts in the Faculty of Education, Rivers State University, Port Harcourt and its reliability was established using Cronbach’s Alpha. The computation yielded an overall coefficient of 0.85 which is above the acceptable threshold of 0.70. Data collected were analyzed using Pearson Product Moment Correlation Coefficient to determine the relationship between the variables. The findings revealed that emergency preparedness and planning, and resource management and mobilization all had strong and positive relationships with educational continuity. Based on the findings, the study concluded that deficiencies in administrative indices correspond with greater disruption to academic programmes, prolonged school closures, and reduced effectiveness of post-disaster recovery efforts. It was recommended, among others, that school administrators, in collaboration with education authorities, should develop and regularly update comprehensive emergency preparedness and response plans tailored to flood risks.